Labour Unions and the Wage Structure: A General Equilibrium Approach - Pettengill, John S. (Review of Economic Studies, 1979)
Journal Article Labour Unions and the Wage Structure: A General Equilibrium Approach Get access John S. Pettengill John S. Pettengill University of Virginia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 4, October 1979, Pages 675–693, https://doi.org/10.2307/2297035 Published: 01 October 1979 Article history Received: 01 September 1975 Accepted: 01 November 1978 Published: 01 October 1979